Evaluation of febuxostat in treating diabetic kidney disease with hyperuricemia: a systematic review and meta-analysis of randomized controlled trials - Lin, Minghao; Zhang, Hui; Wu, Haonan; Zhao, Dexi; Nan, Zheng; Fu, Yujuan (Frontiers in Medicine, 2025)
BackgroundDiabetic kidney disease (DKD) combined with hyperuricemia (HUA) constitutes a pathological state of vicious cycle, where diabetic microvascular complications affect the kidneys and interact with persistent hyperuricemia. This condition significantly accelerates the progression of renal failure and increases all-cause mortality.ObjectiveThis study aims to systematically evaluate the clinical efficacy and safety of febuxostat in treating patients with DKD and HUA via a meta-analysis, thereby providing evidence-based guidance for optimizing clinical medication.MethodsFollowing the PICOS principle, we systematically searched for randomized controlled trials (RCTs) on febuxostat for treating DKD combined with HUA, covering the period from the establishment of each database to June 26, 2025. Studies meeting the inclusion criteria were selected, and a meta-analysis was performed using Review Manager 5.4 software.ResultsA total of 17 RCTs were included, involving 1,300 patients (treatment group n=647, control group n = 653). The results of the meta-analysis showed that the overall effective rate of the febuxostat treatment group was significantly higher than that of the control group (RR = 1.24, 95%CI: 1.17–1.32; Z = 7.17, P < 0.001). In addition, febuxostat significantly reduced serum uric acid (SUA), urinary albumin-to-creatinine ratio (UACR), serum creatinine (Scr), and blood urea nitrogen (BUN) levels, and improved the estimated glomerular filtration rate (eGFR) (P < 0.001 for all indicators).ConclusionThis meta-analysis indicates that febuxostat, when used to treat patients with DKD and HUA, can significantly enhance overall clinical effectiveness and effectively improve key renal function indicators—including SUA, UACR, Scr, BUN, and eGFR. The results of this study showed that when febuxostat is used to treat patients with diabetic nephropathy complicated by hyperuricemia, it achieves a higher overall clinical response rate. It can significantly reduce the levels of SUA, UACR, Scr, and BUN in patients, while improving the eGFR. Additionally, the incidence of adverse reactions associated with febuxostat is lower, suggesting that this drug exhibits favorable clinical safety.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/.